Photodynamic therapy associated with nanomedicine strategies for treatment of human squamous cell carcinoma: A systematic review and meta-analysis - Ferrisse, Túlio Morandin [UNESP]; de Oliveira, Analú Barros [UNESP]; Surur, Amanda Koberstain [UNESP]; Buzo, Helen Sordi [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Fontana, Carla Raquel [UNESP] (Elsevier, 2022)
A systematic review and meta-analysis were conducted about photodynamic therapy (PDT) associated with nanomedicine approaches in the treatment of human squamous cell carcinoma (HSSC). Independent reviewers conducted all steps in the systematic review. For evaluating the risk of bias, RoB 2, OHAT and SYRCLE tools were used. Meta-analysis was performed using a random-effect model (α = 0.05). For PDT against HSSC, Protoporphyrin IX was the photosensitizer, and liposomes were the nanomaterial more frequently used. Photosensitizers conjugated with nanoparticles exhibited positive results against HSSC. Tumors treated with PDT in combination with a nanotechnology drug-delivery system had an increased capacity for inhibiting the tumor growth rate (51.93%/P < 0.0001) when compared with PDT only. Thus, the PDT associated with nanomedicine approaches against HSCC could be a significant option for use in future clinical studies, particularly due to improved results in tumor growth inhibition.
Keywords: Nanomedicine; Nanoparticles; Nanotechnology; Photodynamic therapy; Squamous cell carcinoma